The Role of Financial Technology in Determining the Priorities of Distributing Zakat Using Artificial Intelligence to Achieve Maqasid Al Sharia - Tarshany, Prof. Dr Yasser Mohamed Abdelrahman (Center of Strategic Studies (PUSKAS) BAZNAS, 2025)
Financial technology has entered all aspects of life, so we need to benefit from it in zakat management, especially emerging technologies such as artificial intelligence, which has entered several fields. One of the problems facing zakat management institutions is determining priorities in distributing zakat to legitimate banks, especially with the scarcity of zakat funds relative to the number of those in need of zakat. Therefore, this research aims to present proposals to benefit from artificial intelligence technologies in zakat management and determining priorities according to collecting data related to those in need and analyzing this huge data using machine learning and deep learning techniques. The researcher used the analytical inductive approach, and the results of this research showed the importance of using artificial intelligence in managing zakat funds to achieve the objectives of Islamic law. Therefore, this research is considered a starting point for activating artificial intelligence in zakat management institutions and renewing the means to achieve the objectives of Sharia.